Management of Biocontaminated Waste in the Covid_19 Pandemic - Ramírez Carranza, Krisbell María (2022)
With the arrival of the COVID-19 Pandemic, many activities have been modified, among which are work, student, cultural, and recreational activities. Likewise, the World Health Organization (WHO) has commented that the transmission of this virus is from person to person, as well as the possibility that this virus survives on surfaces for several hours. Given this, the governments of each country have seen the need to propose measures of social isolation or immobilization in order to stop this disease. On the other hand, the arrival of the pandemic has also increased the greater amount of use of products in hospitals, which must be constantly discarded, that is, the waste management system plays an important role there. Years ago, the solid waste and biopollutant management system was inefficient and scarce, which made the pandemic worsen the situation. The objective of this systematic research is to explain the problem of biocontaminated waste management during the COVID_19 pandemic, the qualitative approach research was based on the PRISMA methodology, to obtain information about the development of works on topics related to biocontaminated waste management, For this study, use has been made of databases such as: SCIELO, GOOGLE ACADEMIC, REDALYC AND DIALNET, whose criteria applied were in terms of temporality the last 4 years (2019 - 2022); In addition, regarding the conclusions, the management of biocontaminant waste has not been the most appropriate, but efforts have been made within the collection system, of solid waste, which has allowed the decrease and increase of warehouses for biocontaminant waste, with the purpose to preserve the health of the population and care for the environment.